Design & Narration? : -A research exploring how design and narration, collectively, work as a means to expand the uncharted field of design pedagogy - Ceder, Clara (Institutionen för Bildpedagogik (BI), 2011)
ABSTRACT This text process a design pedagogical research executed in Arvidsjaur during the fall of 2011. The formulation of questions that this study circles around regards how combining design and narration can be used in the development of design pedagogy. Also scrutinized, how did the formulation of this research affect the outcome and what means, in addition their attendance, did the people who partook contribute with? The purpose is to find a pedagogic angle that moves focus away from the finished product and onto other aspects of the design process. To clarify, by investigating how narration adapts as a tool during a design process this research seek to enlighten ways that we comprehend, and make use of, our surroundings while working towards a common - designed - goal. What comes about when gathering a group of people and asking them to represent Arvidsjaur by designing a cup? The material used emanates from observations, narratives, images and finished artifacts – all deriving from a set of workshops held in the city of Arvidsjaur. To partake in the workshops was voluntary and the invite began with the question/statement: Design and narration? An ethnographically inspired method preceded the structure of the study and hence made it impossible to foreordain what would occur before arriving in Arvidsjaur. By placing the gathered material and observations along with a set of selected theories, such as sociocultural learning and social constructionism, I wish to enlighten and point out qualities, along with weaknesses, that this study occupies. Beyond a written contribution, and the work on the field, the research resulted in a number of designed cups. These cups were photographed, processed, and depicted in three different ways – as posters and as a series of photographs. These images were on display during an exhibition at Konstfack in December 2011. My contribution to the exhibition was meant as a continuation on questions regarding design and narration. What happens e.g. with an item when it is displayed ...